Insulin alleviates degradation of skeletal muscle protein by inhibiting the ubiquitin-proteasome system in septic rats - Gao Tao; Yu Wenkui; Tang Shaoqiu; Li Weiqin; Zhu Weiming; Li Ning; Chen Qiyi; Zhang Juanjuan; Li Jieshou (BMC, 2011)
Abstract Hypercatabolism is common under septic conditions. Skeletal muscle is the main target organ for hypercatabolism, and this phenomenon is a vital factor in the deterioration of recovery in septic patients. In skeletal muscle, activation of the ubiquitin-proteasome system plays an important role in hypercatabolism under septic status. Insulin is a vital anticatabolic hormone and previous evidence suggests that insulin administration inhibits various steps in the ubiquitin-proteasome system. However, whether insulin can alleviate the degradation of skeletal muscle protein by inhibiting the ubiquitin-proteasome system under septic condition is unclear. This paper confirmed that mRNA and protein levels of the ubiquitin-proteasome system were upregulated and molecular markers of skeletal muscle proteolysis (tyrosine and 3-methylhistidine) simultaneously increased in the skeletal muscle of septic rats. Septic rats were infused with insulin at a constant rate of 2.4 mU.kg-1.min-1 for 8 hours. Concentrations of mRNA and proteins of the ubiquitin-proteasome system and molecular markers of skeletal muscle proteolysis were mildly affected. When the insulin infusion dose increased to 4.8 mU.kg-1.min-1, mRNA for ubiquitin, E2-14 KDa, and the C2 subunit were all sharply downregulated. At the same time, the levels of ubiquitinated proteins, E2-14KDa, and the C2 subunit protein were significantly reduced. Tyrosine and 3-methylhistidine decreased significantly. We concluded that the ubiquitin-proteasome system is important skeletal muscle hypercatabolism in septic rats. Infusion of insulin can reverse the detrimental metabolism of skeletal muscle by inhibiting the ubiquitin-proteasome system, and the effect is proportional to the insulin infusion dose.